The effect of teaching Islamic education using adaptive learning on developing metacognitive thinking skills for primary school students in Makkah - Al-Osaimi, Reem Khader (Journal of Curriculum and Teaching Methodology, 2022)
The current study aimed to identify the impact of teaching Islamic education using adaptive learning in developing metacognitive thinking skills for female primary school students in Makkah Al-Mukarramah. To verify this, a measure of metacognitive thinking skills was prepared by the researcher, and the validity and reliability of the tools were verified, and lessons were prepared. The jurisprudence topic from the education course for the sixth grade of primary school using adaptive learning, and the researcher used the experimental method to apply the study. The study sample included (50) female students as an experimental group who studied using adaptive learning, (50) female students as a control group who studied in the traditional way through my school platform, and the study tools were applied in practice. Before to verify the equivalence of the two groups, then unit lessons were taught using adaptive learning on the experimental group, then the tools were applied afterwards on the two groups. The study used the statistical program T-Test, SPSS to analyze the results and then interpret them. The study concluded the following: There are statistically significant differences at the level of 0.05 between the mean scores of the female students in the experimental and control groups in the post application of the supracognitive thinking skills scale as a whole, as well as in its sub-skills (the skill of organizing knowledge - the skill of knowing knowledge - the skill of processing knowledge) in favor of the experimental group.